1993
DOI: 10.1002/art.1780360605
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocyte chemotactic and activating factor in rheumatoid arthritis. regulation of its production in synovial cells by interleukin‐1 and tumor necrosis factor

Abstract: Objective. To investigate whether monocyte chemotactic and activating factor (MCAF) contributes to the accumulation of macrophages in the joints of patients with rheumatoid arthritis (RA). Methods. MCAF was measured by radioimmunoassay. MCAF gene expression was determined by Northern blotting and reverse‐transcriptase polymerase chain reaction. Recombinant human MCAF was injected into rabbit joints to evaluate the effect of MCAF on infiltration of macrophages. Results. High levels of MCAF were detected in syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 26 publications
3
57
0
1
Order By: Relevance
“…The pivotal role played by MCP-1 in RA in humans is highlighted by the findings of enhanced production of MCP-1 in serum and/or synovial fluid from patients with RA (33)(34)(35). Moreover, data from studies of animal models suggest that MCP-1 is involved in the pathogenesis of RA (36)(37)(38), and MCP-1 was recently reported to be a sensitive marker of disease activity in patients with juvenile RA (39).…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal role played by MCP-1 in RA in humans is highlighted by the findings of enhanced production of MCP-1 in serum and/or synovial fluid from patients with RA (33)(34)(35). Moreover, data from studies of animal models suggest that MCP-1 is involved in the pathogenesis of RA (36)(37)(38), and MCP-1 was recently reported to be a sensitive marker of disease activity in patients with juvenile RA (39).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the levels of MCP-1 are increased in the blood, synovial fluid, and synovial tissue of patients with RA (7,8). Injection of MCP-1 into rabbit joints resulted in marked macrophage infiltration in the affected joint (8).…”
mentioning
confidence: 98%
“…It was reported that the levels of MCP-1 are increased in the blood, synovial fluid, and synovial tissue of patients with RA (7,8). Injection of MCP-1 into rabbit joints resulted in marked macrophage infiltration in the affected joint (8). Treatment with MCP-1 antagonist before disease onset in an MRL/lpr mouse model of arthritis was shown to prevent the onset of arthritis (9).…”
mentioning
confidence: 99%
“…Synovial tissue is the dominant source of MCP-1/CCL2 production in rheumatoid arthritis (RA), and levels of MCP-1/CCL2 are significantly increased in RA synovial tissue, synovial fluid, and peripheral blood (4). The possible role of MCP-1/CCL2 in monocyte migration toward the joint is supported by the observation that injection of MCP-1/CCL2 into the rabbit joint leads to a clear increase in macrophage numbers (5). There are several reports showing that MCP-1 is crucial for Th1 immune responses, which are important in the pathogenesis of RA as well as the CIA model (6,7).…”
Section: To the Editormentioning
confidence: 99%